Polemik Komisi Penyiaran Indonesia (KPI) dalam Pengawasan Media Baru - Wahyu Kristian Natalia; Alvian Alrasid Ajibulloh (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2023)
Broadcasting technology has developed so rapidly in Indonesia that education about quality programming has become essential for everyone. With advances in technology and information, online and streaming, media such as Youtube and Netflix have had both positive and negative impacts on the people of Indonesia. Many contents contain harmful elements that need to be limited and monitored by the government and related agencies such as the Indonesian Broadcasting Commission (KPI). Therefore, it is deemed necessary for academics to conduct scientific studies or literature studies that focus on KPI issues. This aims to enrich literacy about the role or function of the Indonesian Broadcasting Commission (KPI) in carrying out its duties. This study reveals that the government revises the law on broadcasting according to the development of information and communication technology but still proportionally does not limit freedom of expression so that various parties can feel the adjustment of this law